(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
Quantitative analyses of calcareous nannofossil were carried out on sediments from ODP Hole 964D succession, recovered in the Ionian Sea, Eastern Mediterranean. Results show that the sedimentary sequence, spanning from about 3.5 Ma (Early Pliocene) to the Present, has been investigated through an average sampling resolution of less than 30 kyr. The detailed subdivision into 11 biozones makes it possible to recognize chronostratigraphic the boundaries in the Early Pliocene-Middle Pleistocene interval. Finally, two sedimentary gaps, lasting at least 340 kyr and 120 kyr respectively, have been recognized between the Zanclean and Piacenzian and in the lower part of the Early Pleistocene. SHORT NOTE